Hyperprolinemia as a Clue in the Diagnosis of a Patient with Psychiatric Manifestations - Duarte, M (2018)
Lately, microdeletions of the 22q region, responsible for DiGeorge syndrome or velocardiofacial syndrome, have been increasingly related to neuropsychiatric disorders including schizophrenia and bipolar disorder. These manifestations seem to be related to certain genes located in the hemideleted region such as the proline dehydrogenase (PRODH) and the catechol-o-methyltransferase (COMT) genes. We describe a teenager who started his adolescent psychiatric care presenting cognitive impairment, irritable mood and aggressive behaviour with schizophrenia-like symptoms that scored 153 in the Positive and Negative Symptoms Scale (PANSS) assessment. Worsening of symptoms when the patient was treated with valproic acid, and plasma aminoacids showing an increase in alanine and proline, suggested a mitochondrial involvement of the proline metabolic pathway. Mild dysmorphic features also suggested a possible 22q11 deletion syndrome that was confirmed. A mutation for Hyperprolinemia type I was also detected. Knowledge of the correct diagnosis was crucial for an adequate treatment.